SISTEM SIMULASI EVAKUASI KEBAKARAN BERBASIS MULTI AGEN (FIRE EVACUATION SIMULATION SYSTEM BASED ON MULTY AGENT) - , Freska Rolansa, Dr. Azhari S.N., M.T ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The building is one of place that people do various activities at a certain time. At the time of building fire occurs, all those who are in the building must make the evacuation process in order to avoid the danger of fire. Modeling with Agent is one way to describe the condition of fire in real life, to reduce costs and the danger posed in the event of a fire halls. This model uses Multi-agent approach, which consists of the employeeagent, fire agent and exit dooragent which interact and communicate. Each of the characteristics and behavior of the agent is simulated using the NetLogo in the event of fire halls using the expansion fire scenario, rescue scenario, and evacuation support facilities to evaluation process. Tests carried out on the existing condition of the building and changes the support facilities such as the placement of doors and the addition of the door width scenario. Each of the test scenario performed 5 times with the same parameters and the results will be sought value average number of human survivors and the number of victims affected by the fires as a result of the evaluation of evacuation support facility, while also testing the expansion scenario fire and rescue scenario for look at the characteristics and behavior of fire agent and employee agent in evacuation process.